Building-level and stock-level in contrast: A literature review of the energy performance of buildings during the operational stage - Geraldi, Matheus Soares; Ghisi, Enedir (Energy and buildings, 2020)
•We focused on empirical studies published over the past ten years.•We identified two main research approaches: building-level and stock-level analyses.•The granularity of the energy data and the methods/tools were summarised.•We proposed the definition of the geo-stock and the type-stock.•Conceptual models were drawn to map links and insights in research purposes involved. This paper aimed to review the literature of the past ten years about the energy performance of buildings during their operational stage. The focus of this review was empirical works that examined the energy use in real buildings. An overview of the literature survey is presented. A meta-analysis technique allowed the identification of two approaches of study: building-level analysis and stock-level analysis. The building-level analysis considers the building as the system of study. Otherwise, the stock-level analysis considers a group of buildings as the subject of study while the buildings are elements inside the system. Notable research topics were addressed involving performance gap, energy audit, retrofit savings assessment, Zero Energy Buildings (ZEB), benchmarking, regulations and strategies to overcome climate change. This literature review summarised the level of information of the studies by listing the granularity of the energy performance data according to the purpose of the study. Furthermore, a specific section was dedicated to assemble the methods and tools adopted. Finally, we proposed conceptual models for both approaches (building and stock-level) that outlined the main aspects and dynamics identified in this literature review. Thus, we obtained insights to be investigated in further studies.